Total Knee Arthroplasty with Concomitant Corrective Tibial Osteotomy Using Patient-Specific Instrumentation and Computed Tomography–Based Navigation in Severe Post–High Tibial Osteotomy Valgus Collapse - Koji Shibano, MD, PhD; Yasuo Kunugiza, MD, PhD; Kunihiko Kawashima, MD, PhD; Tetsuya Tomita, MD, PhD (Arthroplasty Today, 2020)
We report the case of a 78-year-old woman with lateral knee osteoarthritis and severe valgus knee deformity after high tibial osteotomy. The patient's severe valgus tibial deformity with a valgus angle of 45° was evaluated using a 3-dimensional bone model, and a closing-wedge osteotomy was planned. Combined total knee arthroplasty and closing-wedge tibial osteotomy were performed using patient-specific instrumentation and a computed tomography–based navigation system. A semiconstrained total knee system with a long stem was implanted for fixation of the osteotomy site in the tibia. The patient was able to walk without pain 2 years postoperatively. The Knee Society Score improved from 13 to 73 points, and the functional score improved from 30 to 65 points. This preoperative planning method and the treatment procedure would be beneficial for clinical decision-making and treatment of severe valgus knee deformities.